2014
DOI: 10.1111/bjc.12041
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: A meta‐analysis and theoretical critique of oxytocin and psychosis: Prospects for attachment and compassion in promoting recovery

Abstract: There are significant problems in interpreting the current evidence base for OXT in psychosis. However, OXT may provide a useful biomarker for exploring mechanisms of change occurring in psychological therapies including compassion-focused therapy (CFT), which through its engagement of the attachment system may directly influence OXT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 94 publications
3
46
1
Order By: Relevance
“…Therefore, we need to find a treatment method that improves negative symptoms and cognitive impairments in schizophrenia. Oxytocin is a neuropeptide hormone that is produced by the hypothalamus and secreted by the posterior pituitary gland; this hormone modulates multiple social cognitive domains such as trust, attachment behavior, stress response, social memory, and the ability to recognize emotions and understand mental states [4,15,25]. Recent studies have found that intranasal oxytocin administered to normal human subjects increased perceived trustworthiness [10, 19,33].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we need to find a treatment method that improves negative symptoms and cognitive impairments in schizophrenia. Oxytocin is a neuropeptide hormone that is produced by the hypothalamus and secreted by the posterior pituitary gland; this hormone modulates multiple social cognitive domains such as trust, attachment behavior, stress response, social memory, and the ability to recognize emotions and understand mental states [4,15,25]. Recent studies have found that intranasal oxytocin administered to normal human subjects increased perceived trustworthiness [10, 19,33].…”
Section: Introductionmentioning
confidence: 99%
“…Self-criticism is a defensive response to deal with feelings of shame (Gilbert, 2010), and although no other studies assessed selfcriticism, decreases in shame and self-criticism are essential in recovery and relapse prevention according to the social mentalities model for psychosis (Gumley et al, 2010). Furthermore, relapse has been associated with greater feelings of self-blame and shame (Gumley et al, 2006); therefore, intervention should focus on the activation of the safeness system (Gumley et al, 2010), which is essential for stress reduction and promotion of social bonding and affiliative behaviours (Gumley, Braehler, & Macbeth, 2014;Gumley, Taylor, Schwannauer, & Macbeth, 2014).…”
Section: Participantmentioning
confidence: 99%
“…At each testing session, 40 IU of oxytocin (Novartis, Switzerland) was self-administered intranasally by alternating insufflations every 20 s between nostrils. This dose of oxytocin has been used in previous clinical trials of oxytocin in schizophrenia (Gumley et al, 2014). Mean time from drug administration to olfactory testing was 139 min (SD = 19 min, range: 111-206 min).…”
Section: Design and Proceduresmentioning
confidence: 99%
“…These studies link oxytocin signaling in the olfactory bulb with olfactory and social functions. Finally, there is growing evidence that oxytocin administration to patients with schizophrenia improves emotion recognition and higher-level social cognition and decreases both positive and negative symptoms (Gumley et al, 2014). Additionally, a recent study that administered 20 IU of oxytocin or placebo twice daily for three weeks to patients with schizophrenia found that oxytocin improved patients' ability to identify pleasant, but not neutral or unpleasant odors (Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%